A high‐reliability alumina‐platinum multilayer system for implantable medical devices. Issue 1 (20th August 2018) - Knudsen, Arne; Makino, Hiroshi; Morioka, Kengo; Otomaru, Hidekazu; Matsumoto, Hiroshi; Satoh, Shingo; Thom, Andrew; Munns, Gordon; Yamamoto, Joyce; Reiterer, Markus
Abstract: A new Pt‐Al2 O3 multilayer composite system has been developed and validated with an Accelerated Life Test (ALT) to confirm its potential for long‐term use in implantable medical devices (IMD). Panels containing over 100 Pt vias were subjected to highly accelerated immersion testing in deionized water at temperatures ranging from 90 to 175°C. Deionized water was employed as it best represents the IMD use environment. Degradation of individual Pt vias was evaluated using fluorescent dye infiltration into the subsurface of the panels. ALT guided refinement of materials and processing to produce a Pt‐Al2 O3 multilayer composite system with promising performance for possible use in implantable devices.